A genome‐wide association study of obstructive heart defects among participants in the National Birth Defects Prevention Study. Issue 8 (22nd April 2022) - Rashkin, Sara R.; Cleves, Mario; Shaw, Gary M.; Nembhard, Wendy N.; Nestoridi, Eirini; Jenkins, Mary M.; Romitti, Paul A.; Lou, Xiang‐Yang; Browne, Marilyn L.; Mitchell, Laura E.; Olshan, Andrew F.; Lomangino, Kevin; et al.
Abstract: Obstructive heart defects (OHDs) share common structural lesions in arteries and cardiac valves, accounting for ~25% of all congenital heart defects. OHDs are highly heritable, resulting from interplay among maternal exposures, genetic susceptibilities, and epigenetic phenomena. A genome‐wide association study was conducted in National Birth Defects Prevention Study participants ( N discovery  = 3978; N replication  = 2507), investigating the genetic architecture of OHDs using transmission/disequilibrium tests (TDT) in complete case‐parental trios ( N discovery_TDT  = 440; N replication_TDT  = 275) and case–control analyses separately in infants ( N discovery_CCI  = 1635; N replication_CCI  = 990) and mothers (case status defined by infant; N discovery_CCM  = 1703; N replication_CCM  = 1078). In the TDT analysis, the SLC44A2 single nucleotide polymorphism (SNP) rs2360743 was significantly associated with OHD ( p discovery  = 4.08 × 10 −9 ; p replication  = 2.44 × 10 −4 ). A CAPN11 SNP (rs55877192) was suggestively associated with OHD ( p discovery  = 1.61 × 10 −7 ; p replication  = 0.0016). Two other SNPs were suggestively associated ( p  < 1 × 10 −6 ) with OHD in only the discovery sample. In the case–control analyses, no SNPs were genome‐wide significant, and, even with relaxed thresholds ( × discovery  < 1 × 10 −5 and p replication  < 0.05), only one SNP (rs188255766) in the infant analysis was associated with OHDs ( p discovery  = 1.42 × 10 −6 ; p replication  = 0.04). Additional SNPs with p discovery  < 1 × 10 −5 were in loci supporting previous findings but did not replicate. Overall, there was modest evidence of an association between rs2360743 and rs55877192 and OHD and some evidence validating previously published findings.